PROFIL PETANI-TENAK SAPI POTONG PADA KELEMBAGAAN KELOMPOK TANI - Sry Yenny Pateda; Umbang Arif Rokhayati (Gorontalo Journal of Equatorial Animals, 2022)
This study aims to determine the characteristics of beef cattle breeders in farmer group development. This research was carried out in Gorontalo Regency in February-June 2018. The method used survey techniques in obtaining primary and secondary data. Determination of the sample is done by multistage sampling. The number of samples is 120 people. The results showed that the age of the farmer was productive and had a basic education of 87%, the average length of the cattle business was 13 years, the number of dependents in the family was 4 people with an average livestock ownership of 4 heads. Characteristics of farmers affect the institutional capacity of farmer groups by 0.280, each age contributes 65%, education 54.6%, length of business 63%, and the number of family dependents 53.5%. The capacity building of beef cattle farmer groups shows that age has a high contribution.